Correction: Millifluidic synthesis of cadmium sulfide nanoparticles and their application in bioimaging. Issue 62 (10th August 2017) - Hong, Liying; Cheung, Tai-Lok; Rao, Nanxi; Ouyang, Qingling; Wang, Yue; Zeng, Shuwen; Yang, Chengbin; Dang, Cuong; Chong, Peter Han Joo; Liu, Liwei; Law, Wing-Cheung; Yong, Ken-Tye
Abstract : Correction for 'Millifluidic synthesis of cadmium sulfide nanoparticles and their application in bioimaging' by Liying Hong, Tai-Lok Cheung et al., RSC Adv., 2017, 7, 36819–36832.